A Novel Thinner Mechanical Keyboard Key Based on the Slider Rocker Mechanism - Hua, Yanbin; Yang, Baotong; Lee, Chew-Tin; Xu, Zhiqiang (Recent Patents on Engineering, 2017)
Background: Patents reveal that a comfortable touch, slim size and light in weight have become a prevailing trend in the design and development of computer keyboard. Current mechanical keyboard has attracted a great attention due to its advanced features especially the need for unique touch and comfort of mechanical key devices in the new era of computer technology. However, there are still shortcomings in the key size, portability and flexibility and also the assembling process. Methods: This paper proposes the novel use of the slider rocker mechanism for the thinner design of the mechanical keyboard key. The mechanism is combined with the snap-in connection to make the key thinner and assembling process simpler. Results: The slider rocker mechanism enables a thinner design of the key by driving the rotational motion through the rotary keycap to initiate the translational motion. This feature also improves the portability and flexibility for the mechanical keyboard. The key assembling process is deemed simpler based on the simple snap-in connection between the switch and the base of the key. The design and operation procedure of this mechanical keyboard key are described in detail. Conclusion: A novel thinner mechanical keyboard key has been developed based on the slider rocker mechanism and snap-in connection between the switch and base of the key to accomplish the reduction of size in the vertical direction of the key, improved portability and flexibility for mechanical keyboard and simpler key assembling process. To our knowledge, this is the first thinner mechanical key in the keyboard based on the new mechanisms of operation.
Keywords: thinner key